Influence of Walking, Manual Techniques, and Elastic Resistance Exercise on Shoulder Posture in Healthy Elderly Individuals - Novotová, Klára; Pavlů, Dagmar (Geriatrics (Basel, Switzerland), 2024)
UNLABELLED: In this study, we investigated the effect of regular walking and its combination with manual techniques/resistance exercise. The position of the shoulder girdle was assessed using the acromion-wall distance (AD). The intervention took place twice a week for 4 weeks. A total of 88 seniors over the age of 60 successfully completed the study. The results showed a statistically significant improvement of AD in the left shoulder within the group that underwent walking combined with resistance exercise. The remaining groups did not show any statistically significant change in AD. BACKGROUND: The world population is rapidly aging; therefore, it is necessary to respond to this challenge in time. One of the typical involutional signs of old age is a hunched posture combined with a forward position of the shoulder girdle. This posture negatively impacts various bodily functions, postural stability, and strain on the musculoskeletal system. OBJECTIVES: We aimed to evaluate the effect of walking and walking combined with manual therapy/resistance exercise on scapular positioning in healthy elderly individuals. METHODS: Participants of experimental groups underwent a 4-week training session that involved walking and manual techniques/resistance training applied 2x/week. Participants of the control group maintained their usual daily habits. RESULTS: Our results showed statistically significant improvement in scapular positioning of the left shoulder in participants who underwent regular walking combined with resistance exercise training. CONCLUSIONS: These results suggest that regular walking combined with resistance training, when properly dosed, may beneficially influence scapular positioning in healthy elderly individuals.
Keywords: elderly; healthy; walking; acromion-wall distance; scapular position; resistance training